Clinical Features and Outcomes of 105 Hospitalized Patients With COVID-19 in Seattle, Washington. (22nd May 2020) - Buckner, Frederick S; McCulloch, Denise J; Atluri, Vidya; Blain, Michela; McGuffin, Sarah A; Nalla, Arun K; Huang, Meei-Li; Greninger, Alex L; Jerome, Keith R; Cohen, Seth A; Neme, Santiago; Green, Margaret L; et al.
Abstract: Background: Washington State served as the initial epicenter of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic in the United States. An understanding of the risk factors and clinical outcomes of hospitalized patients with coronavirus disease 2019 (COVID-19) may provide guidance for management. Methods: All laboratory-confirmed COVID-19 cases in adults admitted to an academic medical center in Seattle, Washington, between 2 March and 26 March 2020 were included. We evaluated individuals with and without severe disease, defined as admission to the intensive care unit or death. Results: One hundred five COVID-19 patients were hospitalized. Thirty-five percent were admitted from a senior home or skilled nursing facility. The median age was 69 years, and half were women. Three or more comorbidities were present in 55% of patients, with hypertension (59%), obesity (47%), cardiovascular disease (38%), and diabetes (33%) being the most prevalent. Most (63%) had symptoms for ≥5 days prior to admission. Only 39% had fever in the first 24 hours, whereas 41% had hypoxia at admission. Seventy-three percent of patients had lymphopenia. Of 50 samples available for additional testing, no viral coinfections were identified. Severe disease occurred in 49%. Eighteen percent of patients were placed on mechanical ventilation, and the overall mortality rate was 33%. Conclusions: During the early days of the COVID-19 epidemic in Washington State, the disease had its greatest impact on elderly patients with medical comorbidities. We observed high rates of severe disease and mortality in our hospitalized patients. Abstract : In this case series of 105 consecutively hospitalized COVID-19 patients, the median age was 69 years, and 55% had 3 or more comorbidities. Severe disease occurred in 49% of patients, and overall mortality was 33%.